Actors and Networks in the Megacity A Literary Analysis of Urban Narratives (Edition 1) - More, Prachi (transcript Verlag, 2017)
This study is a concise introduction to Bruno Latour's Actor-Network Theory and its application in a literary analysis of urban narratives of the 21st century. We encounter well-known psycho-geographers such as Iain Sinclair and Sam Miller, and renowned authors, Patrick Neate and Suketu Mehta. Prachi More analyses these authors' accounts of vastly different cities such as London, Delhi, Mumbai, Johannesburg, New York and Tokyo. Are these urban narratives a contemporary solution to documenting an ever-evasive urban reality? If so, how do they embody "matters of concern" as Latour would have put it, laying bare modern-day "actors" and "networks" rather than reporting mere "matters of fact"? These questions are drawn into an inter-disciplinary discussion that addresses concerns and questions of epistemology, the sociology of knowledge as well as urban and documentary studies.